Arabidopsis thaliana plants challenged with uranium reveal new insights into iron and phosphate homeostasis. Issue 2 (22nd November 2017) - Berthet, Serge; Villiers, Florent; Alban, Claude; Serre, Nelson B. C.; Martin‐Laffon, Jacqueline; Figuet, Sylvie; Boisson, Anne‐Marie; Bligny, Richard; Kuntz, Marcel; Finazzi, Giovanni; Ravanel, Stéphane; Bourguignon, Jacques
Summary: Uranium (U) is a naturally occurring radionuclide that is toxic to plants. It is known to interfere with phosphate nutrition and to modify the expression of iron (Fe)‐responsive genes. The transporters involved in the uptake of U from the environment are unknown. Here, we addressed whether IRT1, a high‐affinity Fe 2+ transporter, could contribute to U uptake in Arabidopsis thaliana . An irt1 null mutant was grown hydroponically in different conditions of Fe bioavailability and phosphate supply, and challenged with uranyl. Several physiological parameters (fitness, photosynthesis) were measured to evaluate the response to U treatment. We found that IRT1 is not a major route for U uptake in our experimental conditions. However, the analysis of irt1 indicated that uranyl interferes with Fe and phosphate homeostasis at different levels. In phosphate‐sufficient conditions, the absence of the cation chelator EDTA in the medium has drastic consequences on the physiology of irt1, with important symptoms of Fe deficiency in chloroplasts. These effects are counterbalanced by U, probably because the radionuclide competes with Fe for complexation with phosphate and thus releases active Fe for metabolic and biogenic processes. Our study reveals that challenging plants with U is useful to decipher the complex interplay between Fe and phosphate.